2013
DOI: 10.1155/2013/357598
|View full text |Cite
|
Sign up to set email alerts
|

Simple and Selective Spectrophotometric Determination of Ofloxacin in Pharmaceutical Formulations Using Two Sulphonphthalein Acid Dyes

Abstract: Two new simple and sensitive extraction-free spectrophotometric methods have been established for the determination of ofloxacin (OFX). The methods are based on ion-pair complex formation reaction between OFX and acidic sulphonphthalein dyes, bromocresol purple (method A), and bromocresol green (method B) in dichloromethane. The experimental variables such as reaction medium, reaction time, and reagent concentration have been carefully optimized to achieve the highest sensitivity. Both dyes react spontaneously… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Several studies were performed for the electrochemical detection of OFL (Table 3) [13][14][15][16][17][18][19]78]. Electrochemical biosensing of OFL was first performed by Zhang et al where an electrochemical immunosensor was developed for OFL detection by employing a polypyrrole film-Au nanoclusters modified GC electrode as a sensor platform and horseradish peroxidase/horseradish peroxidase secondary antibody immobilized on gold nanorods as the detection label [13].…”
Section: (B)mentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies were performed for the electrochemical detection of OFL (Table 3) [13][14][15][16][17][18][19]78]. Electrochemical biosensing of OFL was first performed by Zhang et al where an electrochemical immunosensor was developed for OFL detection by employing a polypyrrole film-Au nanoclusters modified GC electrode as a sensor platform and horseradish peroxidase/horseradish peroxidase secondary antibody immobilized on gold nanorods as the detection label [13].…”
Section: (B)mentioning
confidence: 99%
“…However, it has been shown that 70% of OFL was excreted in unmetabolized form into water environment, leading to negative effects on human health [5]. As a result, many methods have been developed for the determination of OFL, including electrochemical methods [9][10][11][12][13][14][15][16], spectrophotometric methods [17,18], and chromatographic methods [19,20]. However, in spite of their high selectivity and sensitivities (LOD of 0.01-16 µg/ml (≈2.7×10 -8 -4.4×10 -5 M), these techniques are time-consuming, require complex sample procedures and involve the use of large amounts of reagents and organic solvents thus need considerable costs.…”
Section: Introductionmentioning
confidence: 99%
“…The resulting MIL-100(Fe) effectively served as an adsorbent for the extraction of the antibiotic levofloxacin from the aqueous phase [20]. More research technique were reviewed [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37].…”
Section: Quinolones and Fluoroquinolonesmentioning
confidence: 99%
“…They are used to treat infections of the respiratory system, community-acquired pneumonia, urinary tract, bone, and soft tissue [ 6 , 7 ]. Chromatographic approaches [ 8 , 9 ], spectrophotometric methods [ 10 , 11 ], chemiluminescence methods [ 12 , 13 ], and electrochemical methods [ 14 , 15 ] have all been presented for determining OFX and CPFX in various analytical matrices.…”
Section: Introductionmentioning
confidence: 99%